Our Experience with Paired Kidney Exchange Transplantation. (July 2018) - Haberal, Mehmet; Akdur, Aydincan; Karakayali, Feza Yarbug; Ozcelik, Umit; Moray, Gokhan; Kulah, Eyyup; Inal, Ali; Torgay, Adnan; Arslan, Gulnaz
Abstract : Introduction: Paired kidney exchange (PKE) transplantation has gained popularity worldwide as the best alternative for renal recipient candidates who are sensitized to their donors or have ABO incompatible donors. In this study we present our early results of paired kidney exchange transplants. Materials and Methods: We started our PKE transplantation programme in July 2015. Various incompatible pairs were matched depending upon the availability of suitable donors and compatible recipients. Matching and donor allocation was done manually. As far as possible, donors were matched for age and glomerular filtration rate. In a meeting before transplantation, all details of the surgery as well as the legal and ethical requirements were given, informed consent was received. Induction was offered to all patients. Antithymocyte globulin induction therapy was administered at the time of transplantation as well as the third day posttransplant; tacrolimus (target level 8-10 ng/mL), mycophenolate mofetil (1g twice a day) and prednisolone were started as immunosuppressive therapy and tacrolimus was maintained with a target level of 6-8 ng/mL 3 months after the operation. All patients were followed up twice weekly for the first 2 weeks, once weekly for the second 2 weeks, once a fortnight for the second and third months. Data were collected from medical records, including demographic data, follow-up serum creatinine, acute rejections, graft, and patient loss and infections. Results: Seven pairs were matched from July 2015 to September 2017 and we performed 14 PKE (5 women, 9 men) transplants. Mean recipient age was 49.8±11.5 (range: 23-61) and mean donor age was 50.4± 12.4 (range: 38-64) years. Five of the donors were fathers, one of them was a mother, 3 were husbands and 5 were wives. Mean mismatch ratio was 5±1 (range: 3-6). Reason for exchange was ABO incompatibility for 10 patients and positive crossmatch and presence of donor specific antibodies for 4 patients. All were 2-way donations. Median waiting time for getting suitable donor after registration was 3 months. Two of the recipients were retransplanted and desensitization with plasmapheresis was needed for panel reactive antibody positivity. One patient underwent preemptive kidney transplant. Mean serum creatinine level at one month and at third month after transplant were 1.03±0.37 and 0.97±0.25 mg/dL. There were only 2 early biopsy-not-proven acute rejection episodes treated with pulse steroids and 2 urinary tract infections treated with oral antibiotics. In 1 patient external iliac artery was replaced with ePTFE vascular graft due to complete dissection. All patients are alive with no serious complications. Conclusions: ABO incompatibility continues to pose a serious problem for transplantation candidates, especially in kidney and liver transplants. Our small series shows that PKE transplantation is an alternative for patients without a viable living-related donor or deceased compatible donor organ.